2019
DOI: 10.1159/000496181
|View full text |Cite
|
Sign up to set email alerts
|

Common Infections and Target Organs Associated with Chronic Granulomatous Disease in Iran

Abstract: Recurrent severe bacterial and fungal infections are characteristic features of the rare genetic immunodeficiency disorder chronic granulomatous disease (CGD). The disease usually manifests within the first years of life with an incidence of 1 in approximately 200,000 live births. The incidence is higher in Iran and Morocco where it reaches 1.5 per 100,000 live births. Mutations have been described in the 5 subunits of NADPH oxidase, mostly in gp91phox and p47phox, with fewer mutations re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 65 publications
0
15
0
2
Order By: Relevance
“…7,28 In Middle Eastern countries, lymphadenitis is the most common infection overall. 4,29 While Staphylococcus aureus, Serratia marcescens, and Klebsiella spp are common causes of skin and lymph node infections, occasionally no organism is identified. In these cases, careful consideration must be taken to identify more unusual and fastidious organisms (see pathogen-specific considerations below).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…7,28 In Middle Eastern countries, lymphadenitis is the most common infection overall. 4,29 While Staphylococcus aureus, Serratia marcescens, and Klebsiella spp are common causes of skin and lymph node infections, occasionally no organism is identified. In these cases, careful consideration must be taken to identify more unusual and fastidious organisms (see pathogen-specific considerations below).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In addition, they had recurrent pneumonias, associated with persistent elevation in erythrocyte sedimentation rate. ChILD seen in CGD patients could be a sequel to recurrent life-threatening infections, or a result of sterile inflammation due to increased expression of pro-inflammatory molecules in genes encoding polymorphonuclear cells [ 23 , 24 ]. chILD is considered to be a rare pulmonary complication among CGD patients, with few published case reports worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, the average stimulative index of CYBB was found to be much lower than that of CYBA and NCF1, indicating more severe granulocytic disability. The lungs have been found to be the most affected organs, with various and complex manifestations in CGD patients 1,10,11 . Radiologic findings can reveal multiple manifestations for the evaluation of disease progress.…”
Section: Discussionmentioning
confidence: 99%
“…The lungs have been found to be the most affected organs, with various and complex manifestations in CGD patients 1 , 10 , 11 . Radiologic findings can reveal multiple manifestations for the evaluation of disease progress.…”
Section: Discussionmentioning
confidence: 99%